Strategi Komisi Pemilihan Umum Provinsi Sumatera Utara Dalam Meningkatkan Partisipasi Masyarakat Pada Pemilihan Gubernur Sumatera Utara 2018 - Hasibuan, Sri Juniarti; Kadir, Abdul; Nasution, Muhammad Husni Thamrin (PERSPEKTIF, 2018)
Community participation at the time of the North Sumatera Governor Election is a very important aspect so that the General Election Commission uses a special strategy to increase public participation in the Gubernur Pemilihan of North Sumatera. The nature of this research is descrptive. The result of the research shows that the strategy of North Sumatera Provincial Election Commission in increasing the society participation in Sumatera Governor Election 2018 is seen from three stages namely the formulation stage shows there is clarity of socialization plan. The stage of action selection shows the implementation of sosialization to the voters segment with the methode of socialization third stage of resource allocation namely by doing technical guidance to the committee. The constraints experienced by the Election Commission of North Sumatera Province is located on the allocation of human resources is very limited in the region.